Unidades de Polícia Solidária (UPS): análise do modelo de polícia comunitária em João Pessoa/PB sob a ótica dos cidadãos - Souza, Francisco Aclaildo de (2020)
This research had as general objective to make an analysis of the public security policy implemented and based on the community police philosophy, from the residents of the Altiplano, Bancários and Mandacaru neighborhoods, in João Pessoa/PB. The relevance and opportunity of the work is characterized by the need to expand the debate in the search for a solution to public security problems and, in particular, the necessary involvement of the scientific community in contributing to public policies in the sector. In order to know the citizens' perceptions regarding the security policy adopted in the neighborhoods object of this exploratory research, a survey was carried out in a sample of 93 residents, from March to July 2020. The choice of neighborhoods was made by the researcher's accessibility and convenience, in which we sought answers to the assumptions of the existence of a distance between discourse and practice of this public security philosophy, absence of effective participation of residents in community policing and their lack of perception regarding integration with the Community Police. The results revealed a security practice in dissonance with the literature, that this is just a continuation of the traditional form of policing, in which there is no necessary citizen participation at any stage of the project, as well as there is no positive perception regarding the interaction between Community Police and citizens of the surveyed neighborhoods. Due to its exploratory essence, this research did not seek to generalize its results because it only reflects the vision of the residents of the investigated communities. In addition to the present limitations, beside to the exploratory methodology and instruments limited to the sample size, the non-inclusion of security agents is added as an obstacle to the study, due to institutional restrictions, which prevented a broad discussion around the theme and knowledge of perceptions of other Community Police actors. It is recommended to expand the study to the other neighborhoods of João Pessoa/PB and to raise awareness of higher security agencies to participate in this effort for knowledge.